How does a scholar think an act is made and how is it actually done? Some reflections based on the intra-history of the Spanish Law of Education (LOE) of 2006 - Tiana, Alejandro (Historia y Memoria de la Educación, 2016)
The article raises a question frequently addressed by historians of education about the connections and possible discrepancies between political practice and its academic analysis. A researcher may study the processes of making and passing an educational law or, alternatively, may delve into its internal history. The first position favours an objective view, but sometimes makes it difficult to know all of the variables playing a role in the policy-making process. For the purpose of addressing such questions this paper sets out to contrast the images and interpretations underlying academic work with the experience of the actors involved in such processes. The author, relying upon his personal experience in policy-making, reflects upon the tensions between internal and external perspectives that arise when analyzing processes of educational change. The article deals with the internal history of the Law of Education (LOE), providing some keys for facilitating its academic analysis. The processes of preparation, debate, drafting, negotiation and parliamentary discussion of the law are presented and commented on. A number of reflections are included with the aim of helping readers and researchers make the best mixed use of external and internal perspectives in analyzing education policy-making.